Faktor Resiliensi Pasien Amputasi: A Systematic Review - M Ruli Maulana; Tintin Sukartini; Sylvia Dwi Wahyuni (FORIKES, 2021)
Introduction: Someone who has a physical disability will certainly affect mental health. Therefore we need the ability to be able to adapt so that it can restore the quality of life. Objective: To analyze resilience factors in post-amputation patients. Methods: The database used in this study were Scopus, SAGE, and Cambridge and limited to the last 5 years of publication from 2016 to 2020, full-text articles, and in English. The keywords used were